Catalyst-free synthesis of 3-hydroxyimidazo[1, 2-a]pyridine zwitterion derivatives via the three-component reaction of ethyl glyoxalate, 2‑aminopyridines and cyclic 1, 3-dicarbonyls. Issue 19 (10th May 2017) - Ghandi, Mehdi; Moshtaghi, Parham; Abbasi, Alireza
Graphical abstract: Highlights: General protocol for the synthesis of 3-hydroxyimidazo[1, 2- a ]pyridine zwitterions. Different behavior of phenylglyoxal and ethyl glyoxalate toward 2-aminopyridines. Catalyst-free method for the synthesis of zwitterion derivatives. Abstract: The three-component reaction of ethyl glyoxalate, 2-aminopyridines, and cyclic 1, 3-dicarbonyl compounds such as 4-hydroxycoumarin, N, N- dimethylbarbituric acid and 4-hydroxy-6-methyl-2 H -pyran-2-one is described for the synthesis of 3-hydroxyimidazo[1, 2- a ]pyridine zwitterion derivatives.